Glenohumeral internal rotation deficit in young asymptomatic elite swimmers - Standoli, J. P.; Candela, V.; Bonifazi, M.; Gumina, S. (Journal of Athletic Training, 2024)
Context Glenohumeral internal rotation deficit (GIRD) may affect overhead athletes and contribute to shoulder injury. Objectives To assess data on passive shoulder range of motion (ROM) in young elite swimmers and to determine the prevalence of anatomical and pure GIRD (aGIRD and pGIRD, respectively) in a large sample size of asymptomatic elite swimmers with a new classification method. Design Cross-sectional study. Setting Research laboratory. Patients or Other Participants A total of 752 asymptomatic elite swimmers were recruited by voluntary participation (391 males and 361 females; mean age, 15.88 ± 2.31 years). Passive glenohumeral rotational ROM was measured bilaterally to investigate the prevalence of aGIRD and pGIRD. Evaluations were performed with athletes at rest before any training or competition. Main Outcome Measure(s) Glenohumeral internal rotation deficit and associated aGIRD and pGIRD in elite youth swimmers by identifying a standard classification procedure. Results Glenohumeral internal rotation deficits were found in 136 participants (18.1%). Anatomical GIRD was present in 28 cases (3.7%), whereas pGIRD was observed in 108 cases (14.4%). No significant differences were found regarding GIRD between sex, age, age group, years of training, breathing side, and distance. Swimmers with pGIRD showed significantly less dominant internal rotation, total ROM, and external rotation gain (P < .01) than swimmers with aGIRD; conversely, swimmers with aGIRD showed significantly less nondominant internal rotation, external rotation, and total ROM than swimmers with pGIRD (P < .01). Conclusion Glenohumeral internal rotation deficit is a relatively common condition in asymptomatic elite youth swimmers; as to not overestimate this condition, aGIRD and pGIRD have to be distinguished. Although they play a role, the respiratory side, dominant limb, and crawl did not have a significant impact on an elite swimmer with GIRD. Key Points - Glenohumeral internal rotation deficit (GIRD) is one of the most common musculoskeletal findings in overhead athletes and most often correlates with an increased incidence of shoulder injury.